2020
DOI: 10.3390/app10072571
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Spectroscopic Investigation of Different Soil Fractions as Affected by Soil Management

Abstract: The interaction of organic matter with the finest soil fractions (<20 μm) represents a good way for its stabilization. This study investigates the effects of conventional (CT), minimum (MT), and no (NT) tillage, fertilization, and non-fertilization, and soil depth (0–30, 30–60, and 60–90 cm) on the amount of organic carbon (OC) in four soil fractions. Diffuse reflectance infrared Fourier transform spectroscopy (DRIFT) was performed to obtain information about the OC quality and the mineralogical composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…While Hossler [44] showed that the newly created (constructed) wetland had a higher soil bulk density, less moisture content, plant biomass, or SOC than the natural wetlands. The opposite results might indicate that wetland age was also an important factor affecting the soil physical properties and the OM accumulation level [45]. In the surface sediments, the contents of the C and N fractions in invaded habitats were prominently higher than those in normal wetland habitat.…”
Section: Organic Matter In the Wetland Habitatsmentioning
confidence: 89%
“…While Hossler [44] showed that the newly created (constructed) wetland had a higher soil bulk density, less moisture content, plant biomass, or SOC than the natural wetlands. The opposite results might indicate that wetland age was also an important factor affecting the soil physical properties and the OM accumulation level [45]. In the surface sediments, the contents of the C and N fractions in invaded habitats were prominently higher than those in normal wetland habitat.…”
Section: Organic Matter In the Wetland Habitatsmentioning
confidence: 89%
“…This SI collects 12 original contributions focused on soil use and management, soil conservation, as well as on the impact of some pollutants on the soil. Specifically, the SI collects nine research papers [10][11][12][13][14][15][16][17][18], two reviews [19,20] and one methodological work [21]. Eight of the twelve manuscripts considered the effects of soil use and management (topic I) [10][11][12][13][14][15][16]21], while the remaining four [17][18][19][20] evaluated the impact of some soil contaminants (e.g., crude oil, tungsten, copper and polycyclic aromatic hydrocarbons) (topic II).…”
Section: Overview Of This Special Issuementioning
confidence: 99%
“…Regarding the aforementioned nine investigations (i.e., research papers), seven were carried out in the field [10][11][12][13][14][15][16], while the others accounted for pot [17] or microcosm [18] experiments. From a geographical point of view, five "field open-air" investigations were carried out in Italy (three in the south [12,13,16], one in the center [15] and one in the north [10] of Italy), while the remaining investigations were in Brazil [14] and China [11].…”
Section: Overview Of This Special Issuementioning
confidence: 99%
“…The soil samples were gently crushed and passed through a 2 mm sieve to obtain the fine fraction. Four particle size fractions were separated by ultrasonic dispersion and wet sieving, using the fractionation method described by De Mastro et al [22]. This method is based on the physical procedure of Bornemann et al [34] for the fractionation of macro-(A: 2000-250 µm) and microaggregate fractions (B: 250-53 µm), and coarse silt-sized (C: 53-20 µm) and free fine silt plus clay fractions (D: <20 µm).…”
Section: Particle Size Physical Fractionation and Soil Organic Mattermentioning
confidence: 99%
“…The dynamics of SOC is also influenced by tillage practices and soil depth, as demonstrated by the observation that continuous tillage can inhibit the formation of microaggregates responsible for the stabilization of OM [21,22].…”
Section: Introductionmentioning
confidence: 99%